Studi Penggunaan Flukonazol pada Pasien HIV/AIDS dengan Infeksi Oportunistik Jamur: Penelitian di RSUD Dr. Saiful Anwar - Irsan Fahmi Almuhtarihan; Didik Hasmono; Hidajah Rachmawati; Agus Sunarko (MPI (Media Pharmaceutica Indonesiana), 2019)
AIDS is characterized by a transition of opportunistic infections. The most common opportunistic infection is candidiasis with prevalence among HIV patients between 80% to 95%. Fluconazole is the main treatment for candidiasis, but combination with nystatin is often done. This study aims to determine the pattern of fluconazole dosages, dosage forms, and combinations given to HIV/AIDS patient with opportunistic fungal infection. This observational retrospective study was conducted on HIV/AIDS patients who were hospitalized with opportunistic fungal infections in the period of January 1st, 2015 to December 31st, 2015 who received fluconazole. Thirty-five patients were included in this study. Fluconazole monotherapy was used by 21 patients (43%), while combination therapy with nystatin was used by 28 patients (57%). Fluconazole monotherapy was generally preceded by the loading dose (1×400 mg) IV drip followed by maintenance doses (1x200 mg) IV drip in 6 patients (24%), whereas the combination of fluconazole and nystatin was generally used as fluconazole (1×200 mg) IV drip and nystatin (3×300,000 IU) PO in 7 patients (14%). Oral fluconazole was mostly (86%) given less than five days, whereas fluconazole IV drip was mostly (43%) given for 6-10 days. The patterns of fluconazole dosages, dosage forms, and combinations given to HIV/AIDS patient with opportunistic fungal infection was appropriate.